THE CORRELATION BETWEEN VOCABULARY MASTERY OF THE SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU AND THEIR READING COMPREHENSION - Fattah Afiq; Rumiri Aruan; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was purposed to discover whether there was a significant correlation between vocabulary mastery of English Study Program FKIP Universitas Riau and their reading comprehension. The population was the second semester of English Study Program FKIP Universitas Riau. The sample was chosen by cluster random sampling and there were 2A as the sample. Vocabulary test was used to find out the students’ vocabulary mastery meanwhile reading comprehension test was use to find out students’ reading comprehension. The gained data of this research was analyzed by using Pearson Product Moment’s Formula which supported by SPSS 25.00 program. The results showed that Rxy = 0,788 < Rt = 0,318, it is possible to conclude that vocabulary mastery and reading comprehension has correlation. Moreover, the null hypothesis (Ho) is rejected, and it can be confirmed that there is a high significant correlation between reading comprehension and vocabulary mastery of the students. So, there was a positive correlation between vocabulary mastery and reading comprehension of the second semester students of English Study Program FKIP Universitas Riau. The gained determination coefficient (R square) was 62.1% which means that vocabulary explained only 62.1% to reading comprehension.Keywords: Correlation, Vocabulary Mastery, Reading Comprehension